Disease surveillance and risk factors affecting mortality of captive cirl buntings (Emberiza cirlus) in a translocation for conservation purposes. Issue 2 (8th April 2021) - Fountain, Kay; Chang, Ruby; Laven, Carl; Gregson, Joanne; Jeffs, Cath; Molenaar, Fieke; Vaughan‐Higgins, Rebecca; Evans, Andy; Carter, Ian; Sayers, Ghislaine; Pocknell, Ann; Sainsbury, Anthony
Abstract: Cirl buntings in the UK were translocated over a 5‐year period by collecting chicks from the residual population, hand‐rearing and releasing them at a site in Cornwall with the aim of establishing a second breeding population. Because mortality and morbidity during captivity restrict the number and fitness of individuals available for release, selected parasites were monitored in the captive chicks, and all deaths were investigated by autopsy, histopathology and bacteriology. Risk factors associated with captive deaths were analysed. Annual mortality during captivity ranged from 4% (3 of 75 chicks in 2006) to 42% (26 of 73 in 2007) of chicks collected. Infectious disease associated with immunosuppression was an important factor in many deaths, and chicks collected with lower body weight were at greater risk of mortality. These findings emphasise the need for rigorous monitoring of all aspects of captive care during passerine translocations and provide evidence‐based recommendations for future projects.